The Role of Transformational Leadership Style and Work Life Balance on Employee Job Satisfaction at Bank BJB Cirebon - Nadya Raffa Nabillah; Noveria Sujijawati (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the role of Transformational Leadership Style and Work Life Balance on Job Satisfaction of Bank BJB Cirebon City employees. The study uses an associative quantitative approach with a cross-sectional design. The study population was 101 employees, and all were sampled using a saturated sampling technique. Data collection was carried out through a questionnaire with a Likert scale and analyzed using IBM SPSS Statistics 26 through validity tests, reliability tests, classical assumption tests, multiple linear regression, F tests, t tests, and coefficients of determination. The F test value of 459.935 with a significance of 0.001 (<0.05) indicates that the regression model used is classified as fit or feasible. Then the results of the first hypothesis test indicate that transformational leadership style plays a positive and significant role in job satisfaction. While the results of the second hypothesis test indicate that Work Life Balance plays a positive and significant role in job satisfaction. The Adjusted R Square value of 0.902 indicates that transformational leadership style and work life balance contribute 90.2% to job satisfaction, while the rest is played by other variables outside the model.